Invariant natural killer T cells minimally influence gut microbiota composition in mice - Qiaochu Lin; Meggie Kuypers; Zhewei Liu; Julia K Copeland; Donny Chan; Susan J Robertson; Jean Kontogiannis; David S Guttman; E. Kate Banks; Dana J Philpott; Thierry Mallevaey (Gut Microbes)
Invariant Natural Killer T (iNKT) cells are unconventional T cells that respond to glycolipid antigens found in microbes in a CD1d-dependent manner. iNKT cells exert innate-like functions and produce copious amounts of cytokines, chemokines and cytotoxic molecules within only minutes of activation. As such, iNKT cells can fuel or dampen inflammation in a context-dependent manner. In addition, iNKT cells provide potent immunity against bacteria, viruses, parasites and fungi. Although microbiota-iNKT cell interactions are not well-characterized, mounting evidence suggests that microbiota colonization early in life impacts iNKT cell homeostasis and functions in disease. In this study, we showed that CD1d−/− and Vα14 Tg mice, which lack and have increased numbers of iNKT cells, respectively, had no significant alterations in gut microbiota composition compared to their littermate controls. Furthermore, specific iNKT cell activation by glycolipid antigens only resulted in a transient and minimal shift in microbiota composition when compared to the natural drift found in our colony. Our findings demonstrate that iNKT cells have little to no influence in regulating commensal bacteria at steady state.Abbreviations: iNKT: invariant Natural Killer T cell; αGC: α-galactosylceramide